TA CLONING PARTIAL ALBUMIN GENE AND ITS TEST FOR SUPPORTING PHARMACOGENOMIC DETECTION DEVELOPMENT - Effendi, Rinal; Putri Kumala, Ajeng; Marti Abna, Inherni; Yurika, Oktri; Desriani, Desriani (Jurnal Pendidikan Matematika dan IPA, 2024)
DNA recombinant technology is a tool that could support thedevelopment of pharmacogenomic detection such as for CYP2D6 copy number detection application. The housekeeping gene was identified as an internal control alternative for the copy number of the CYP2D6 detection component. There are many kinds of housekeeping genes, including albumin. In this report, we have successfully TA-cloned partial albumin to support the development of CYP2D6 copy number detection. TA-cloning was successfully confirmed with white-blue methods in media LB + ampicillin + IPTG + X-Gal and with colony PCR methods. Further, we made a standard curve with this recombinant plasmid to evaluate albumin qPCR efficiency and showed high-efficiency qPCR 0,9914 (99%). Based on the CYP2D6 copy number developed, the test in this study showed low concordance with high reproducibility Long PCR, indicating that the nucleotide base area of albuminand CYP2D6 in this studywas not recommended for CYP2D6 gene multiplication detection.